Portal Vein Thrombosis in a 21-Year-Old Man with Membranoproliferative Glomerulonephritis and Nephrotic Syndrome - Ilya Seleznev; Dinara Jumadilova; Assiya Naushabayeva; Kairat Kabulbayev; Gulaiym Karashasheva; Francesca Cainelli (Case Reports in Nephrology)
Membranoproliferative glomerulonephritis, one of the main causes of nephrotic syndrome, is associated with a state of hypercoagulability that leads to increased risk of thrombotic events. Portosystemic collaterals may reopen due to reversal of the flow within the existing veins and be a presenting feature of thrombosis. We describe a patient who presented with large portosystemic collaterals and signs of portal hypertension and was subsequently found to be affected by membranous proliferative glomerulonephritis. Proteinuria and microscopic haematuria in a patient with signs of portal hypertension and no pre-existing liver disease should raise the suspicion of an underlying kidney disease.